2010
DOI: 10.1108/00251741011014481
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and business performance in the pharmaceutical sector of Jordan

Abstract: Purpose -The purpose of this study is to empirically test the relationship between intellectual capital (i.e. human capital, structural capital, relational capital) and business performance within the pharmaceutical sector of Jordan. Design/methodology/approach -A valid research instrument was utilized to conduct a survey of 132 top-and middle-level managers from all 15 members of the Jordanian Association of Pharmaceutical Manufacturers. Findings -A correlation and path analysis were conducted to ascertain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
376
11
37

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 451 publications
(504 citation statements)
references
References 57 publications
43
376
11
37
Order By: Relevance
“…The study did not incorporate non-financial measures of performance or other factors that affect the relationship. Shabarati, Jawad, and Bontis (2010) in their study on pharmaceutical companies in Jordan reported a positive relationship on isolated effect of intellectual capital components and performance. Similarly, Ngari, Kamau, and Gichira's (2011) study on Kenya pharmaceutical companies, demonstrated that isolated effect of intellectual capital components had positive effect on performance.…”
Section: Intellectual Capital and Corporate Performancementioning
confidence: 99%
“…The study did not incorporate non-financial measures of performance or other factors that affect the relationship. Shabarati, Jawad, and Bontis (2010) in their study on pharmaceutical companies in Jordan reported a positive relationship on isolated effect of intellectual capital components and performance. Similarly, Ngari, Kamau, and Gichira's (2011) study on Kenya pharmaceutical companies, demonstrated that isolated effect of intellectual capital components had positive effect on performance.…”
Section: Intellectual Capital and Corporate Performancementioning
confidence: 99%
“…This is due to the fact that educated, skilled, and experienced staff tend to establish better relationships with a wide range of partners (thus capitalising on relational assets), and improve the efficiency of business processes (thus generating structural capital) [Cabrita, Bontis, 2008;Kim et al, 2012]. Other authors, on the contrary, insist that relational capital ultimately makes the highest contribution to companies' financial performance [Reed et al, 2006;Huang, Hsueh, 2007;Sharabati et al, 2010]: reliable client and supplier relations allow for cutting costs and increasing sales, thus improving the company's overall competitiveness. Henri Inkinen [Inkinen, 2015] presented a thorough review of empirical studies on the role of human capital comprising more than fifty relevant works.…”
Section: Elements Of Intellectual Capital and Companies' Performancementioning
confidence: 99%
“…An analysis of previously conducted studies (Table 1) reveals that the most commonly used methods for assessing Russian companies' intellectual capital are the VAIC model and the proxy indicators technique based upon it. As part of the third approach, intellectual capital elements are assessed by surveying company managers using specially designed questionnaires [Sharabati et al, 2010;Suraj, Bontis, 2012]. According to the proponents of this methodology, it allows for conducting an integrated assessment of the overall intellectual capital and its specific elements [St-Pierre, Audet, 2011], so it seems to be best suited for the purposes of our study.…”
Section: Study Toolsmentioning
confidence: 99%
“…We also examined the root mean square error of approximation (RMSEA), which should be below .08 for an acceptable fit (Diamantopoulos and Singuaw, 2000). We focused on these measures as they have been widely used in previous studies (Hsu and Sabherwal, 2012;Sharabati et al, 2010;Shih et al, 2010). We developed our measurement process using the statistical software "R" to develop descriptive statistics, exploratory factor analysis and Cronbach's Alpha analysis, where confirmatory factor analysis and SEM analysis were developed using "LISREL 8.80.…”
Section: Pilot Test Of Questionnairementioning
confidence: 99%